Interopera-impossibility? - Greene, Jan (Managed Care, 2019)
CMS wants Medicare Advantage plans to provide enrollees with immediate access to their health information starting in 2020. But you can't always get what you want. Insurers are especially worried about programming interface software that will allow their databases to share information with third parties, such as mobile apps.